2007
DOI: 10.1002/jbm.a.31246
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo biological responses of plasma‐sprayed hydroxyapatite coatings with posthydrothermal treatment

Abstract: This study was undertaken to evaluate the effect of post-hydrothermal treatment on the biological responses of the plasma-sprayed hydroxyapatite (HA)-coated Ti-6Al-4V implant system both in vitro and in vivo. After hydrothermal treatment, the HA coating (HAC) shows the high mechanical strength and indices-of-crystallinity, denser microstructure, lower concentrations of amorphous and impurity phases, when compared with the as-sprayed HAC. The in vitro cell-culture studies, using UMR106 osteoblast-like cell, dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…The in vitro biocompatibility tests demonstrated that crystalline HA has a considerably lower dissolution rate and the presence of Ti-OH bonding can further enhance the bioactive properties of the HA coating by promoting the osteointegration process. 30,32 In our resent study, the HT-HACs showed a statistically higher extent of new bone apposition than the as-sprayed HACs, 33 and it could further achieve the initial fixation of implants in clinical use. Fig.…”
Section: Self-healing Effect Of the Hydrothermal Crystallizationmentioning
confidence: 95%
See 1 more Smart Citation
“…The in vitro biocompatibility tests demonstrated that crystalline HA has a considerably lower dissolution rate and the presence of Ti-OH bonding can further enhance the bioactive properties of the HA coating by promoting the osteointegration process. 30,32 In our resent study, the HT-HACs showed a statistically higher extent of new bone apposition than the as-sprayed HACs, 33 and it could further achieve the initial fixation of implants in clinical use. Fig.…”
Section: Self-healing Effect Of the Hydrothermal Crystallizationmentioning
confidence: 95%
“…19,33 Furthermore, the improved bonding strength of HT-HACs which resulted from its dense microstructure and enhanced HAC/substrate adhesion is possible to provide better mechanical fixation of the implants without some dissociation Fig. 9.…”
Section: Bonding Strength and Failure Mechanismmentioning
confidence: 99%
“…The subcutaneous tissue, muscles and ligaments were dissected to expose the lateral external surface of the diaphyseal bone. An end-cutting bur was used to drill make a crack 1.5 mm in diameter with manual rotating movements to avoid overheating and necrosis of the bone tissue [24]. Plates of uncoated and coated Ti of 3.0 ×1.0 × 1.0 mm were implanted in tibia of rats.…”
Section: Anesthesia and Surgery Techniquementioning
confidence: 99%
“…In order to improve the bone-bonding ability of titanium, it is a good method that titanium substrates are coated with bioactive ceramics. Many modification techniques can be used to coat bioactive materials onto a titanium surface, such as plasma spraying [1], radio frequency (RF)-sputtering [2], and electrochemical techniques [3]. For example, titanium-alloy implants with plasma-sprayed hydroxyapatite (HA) coatings have been shown the direct physicochemical bone bonding and reliable interface strength to surrounding bone tissue.…”
Section: Introductionmentioning
confidence: 99%